Program Edukasi mengenai Triple Eliminasi untuk Mencegah Penularan HIV, Hepatitis B, dan Sifilis pada Ibu Hamil - Miftah Chairunnisa; Arum Seftiani Lestari; Paskalia Tri Kurniati; Khairulisni Saniati; Atri Rudtitasari (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
The Triple Elimination Program is an important initiative to prevent the transmission of HIV, Hepatitis B, and Syphilis from mother to child during pregnancy, childbirth, and breastfeeding. The goal of this program is to improve the well-being of mothers and babies, while reducing the transmission rate of these diseases that can endanger the health of both. This community service activity was carried out in Sungai Maram Village, Sintang, on July 16, 2025. The main target of this activity was 40 pregnant women, who were the objects of the infectious disease education and prevention program. To ensure the effectiveness of this activity, participant knowledge was measured using a pretest and posttest method. The pretest was conducted before the material was delivered to determine the participants' initial level of knowledge, while the posttest was conducted after the material was delivered to measure the extent of the participants' understanding of the information that had been presented. The material presented in this activity covered the three main diseases that are the focus of Triple Elimination, namely HIV, syphilis, and hepatitis B. In addition, participants were also provided with information on ways to prevent transmission of these diseases during pregnancy, childbirth, and breastfeeding. In addition, participants were taught the importance of regular checkups, proper medication use, and steps to protect the health of mothers and babies. The results of this activity are expected to raise awareness among pregnant women about the importance of preventing infectious diseases and provide useful information to maintain their health and that of their unborn babies. Thus, this program not only prevents disease transmission but also contributes to the overall well-being of the community. Furthermore, this activity also aims to strengthen community participation in preventing the transmission of HIV, Hepatitis B, and Syphilis.